Controle da ferrugem asiática (Phakopsora pachyrhizi Sydow & Sydow) com uso de fungicidas em cultivares de soja - Gazzoni, André (2020)
Brazil is the world's second largest producer of soybeans, behind the United States. These two countries together produce 66% of all soy in the world. Soy is one of the main Brazilian agricultural products, and the production chain impacts on agribusiness from the economic, social, environmental, technological and even political perspectives. The crop is used for human and animal food, in the generation of biofuels, drugs and medicines. Soy can be vulnerable to diseases, with significant losses that can reach 100% when no control method is adopted. Among the diseases, Asian rust (Phakopsora pachyrhizi) from soybeans is one of the most aggressive and has a potential for losses greater than 80% in different regions of the world. The objective of the work was to analyze the efficiency and financial viability of fungicides applied in soybean cultivars to control Asian rust. The experiment was installed in the field in the municipality of Cruzaltense / RS in the agricultural year 2018/19 in a randomized block design (DBC), arranged in a 3 x 6 factorial scheme, with four replications. In factor A, soybean cultivars (BRS 6203RR; TMG7262RR; Zeus 55I57RSF IPRO) were allocated and in B fungicides (control; [trifloxystrobin + protioconazole]; [triflo. + prot.] + mancozebe; [triflo. + prot.] + copper oxychloride; [triflo. + prot.] + chlorothalonil; and [triflo. + prot.] + mancozeb + copper oxychloride + chlorothalonil). The plots were composed of 9 lines spaced at 0.50 m, with a length of 5 m. Three fungicide applications were carried out starting at the R1 / R2 stage, repeating the application every 18 days. The spray volume applied was 200 L ha-1 using a precision spray propelled by CO2, which operated at a constant pressure of 2 bar. The incidence and severity of soybean rust after the application of treatments were evaluated. The number of pods per plant and the number of grains per pod were determined in the pre-harvest of soybeans. After harvesting, grain yield (kg ha-1), 1000 grain weight and seed germination were evaluated. Subsequently, the financial viability analysis of the results was carried out. It was observed that the highest grain yield was obtained with application of [trifloxystrobin + protioconazole] + chlorothalonil for the cultivar Zeus 55I57RSF IPRO differing statistically from the control treatments without fungicide and [trifloxystrobin + protioconazole] + mancozebe. For the cultivar BRS 6203 RR, the use of [trifloxystrobin + protioconazole] + mancozebe + chlorothalonil + copper oxychloride was superior to the control without fungicide, but equal to the other treatments. For the cultivar TMG7262 RR there was no statistical difference for the grain yield variable in all treatments. The application of fungicides to control Asian rust of the cultivar TMG 7262 RR was not financially viable, that is, the difference in grain yield resulting from the application of fungicide was not sufficient to obtain a higher financial return than the control without fungicide application. The multisite fungicides mancozebe, copper oxychloride and chlorothalonil, reduce the severity of Asian rust when compared to the fungicides of action at a specific site [trifloxystrobin + protioconazole] isolated for the cultivars BRS 6203 RR and Zeus 55I57RSF IPRO.